2010
DOI: 10.3164/jcbn.09-98
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oryzanol and Ferulic Acid on the Lipid Metabolism and Antioxidative Status in High Fat-Fed Mice

Abstract: The comparative effects of oryzanol and ferulic acid on the lipid metabolism and antioxidative status of high fat-fed mice were investigated. The mice were given a diet containing 17% fat (HF), supplemented with oryzanol (HF-O) or ferulic acid for 7 weeks. The control mice (NC) were fed with normal diet. The HF mice exhibited increased body weight gain, plasma and hepatic total cholesterol and triglyceride concentrations, and lipid peroxidation rate, and reduced high-density lipoprotein cholesterol level. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 27 publications
4
51
1
Order By: Relevance
“…In the present study, serum VLDL levels were notably raised in HFD control group, whereas FA treatment significantly decreased the level of VLDL. Finding of our investigation is in line with the results of previous studies which showed that administration of reduced plasma triglyceride, free fatty acid, and total cholesterol in diabetic rats (Jin Son et al, 2010[20]; Sri Balasubashini et al, 2003[46]). Furthermore, FA has an ability to inhibit cholesterol synthesis via competitive inhibition of HMG-CoA reductase (Kim et al, 2003[30]).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, serum VLDL levels were notably raised in HFD control group, whereas FA treatment significantly decreased the level of VLDL. Finding of our investigation is in line with the results of previous studies which showed that administration of reduced plasma triglyceride, free fatty acid, and total cholesterol in diabetic rats (Jin Son et al, 2010[20]; Sri Balasubashini et al, 2003[46]). Furthermore, FA has an ability to inhibit cholesterol synthesis via competitive inhibition of HMG-CoA reductase (Kim et al, 2003[30]).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, γ-oryzanol, GABA, phytic acid, tocols, and policosanol were significantly higher in a germinated rice sample than that of the non-germinated one. γ-oryzanol, GABA, and phytic acid have hypolipidemic, hypoglycemic, and anti-obesity effects [4,7,37,38,39]. The tocols and policosanol possess antioxidative and antidiabetic property [4,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Orz and FA are able to improve the plasma and hepatic lipid profile by increasing faecal lipid excretion [14]. The available evidence suggests that intakes of 1.5–2.0 g of plant sterols may lower blood LDL-cholesterol by an average of 8.5%–10% [56,57].…”
Section: Anti-obesity Effects Of γ-Oryzanolmentioning
confidence: 99%